2007
DOI: 10.1038/sj.ejcn.1602848
|View full text |Cite
|
Sign up to set email alerts
|

α-Lactalbumin-rich infant formula fed to healthy term infants in a multicenter study: plasma essential amino acids and gastrointestinal tolerance

Abstract: Objective: To evaluate the efficacy and safety of an a-lactalbumin-enriched formula with a protein profile and total protein concentration closer to human milk (HM) and lower than conventional formulas. Subjects/methods: Two hundred and sixteen healthy, term infants, p14 days post-natal age were enrolled and 166 (76.9%) completed the study. Timed post-prandial plasma essential amino-acid levels were determined after 8 weeks of ad libitum study feeding. Study events were assessed every 2 weeks. Results: At 8 we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
58
0
1

Year Published

2010
2010
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 66 publications
(63 citation statements)
references
References 28 publications
4
58
0
1
Order By: Relevance
“…The effect of a-lactalbumin on GI side effects first came up in the trial by Lien et al (2004) and was confirmed by Davis et al (2008). This study confirms the beneficial effect in a population of children with colic.…”
Section: Discussionsupporting
confidence: 72%
See 2 more Smart Citations
“…The effect of a-lactalbumin on GI side effects first came up in the trial by Lien et al (2004) and was confirmed by Davis et al (2008). This study confirms the beneficial effect in a population of children with colic.…”
Section: Discussionsupporting
confidence: 72%
“…This EF, slightly reduced in protein content and enriched in a-lactalbumin, guaranteed appropriate weight and height gains in this population of infants with colic, confirming the nutritional adequacy of the protein profile (Lien et al, 2004;Davis et al, 2008). The study failed to show any reduction in colic.…”
Section: Discussionmentioning
confidence: 73%
See 1 more Smart Citation
“…All but 2 studies included infants of both sexes, while Fomon et al [10] and Carnielli et al [11] enrolled male infants only. Ten of 14 studies aimed to investigate the suitability and safety of the formulae with a focus on protein and carbohydrate contents [2,10,12,13,14,15,16,17,18,19], while studies focused on fat composition aimed to investigate fat or mineral balances [11,20,21]. Schmelzle et al [17] and Lasekan et al [19] studied modified carbohydrate components in formulae.…”
Section: Resultsmentioning
confidence: 99%
“…The studies of Koo et al [20], Kennedy et al [21], and Carnielli et al [11] investigated formulae with modified fat contents. Most of the included studies focused on the protein component [2,10,12,13,14,15,16,17]. …”
Section: Resultsmentioning
confidence: 99%